(untitled) (Minerva, 2019)
In the fourth century, Christian writers polarized the binary opposition between Christians and pagans in order to clarify and strengthen the Christian self-identity. However, there was a wide grey area between hard-line polytheism and hard-line Christianity in Late Antiquity. In scholarly literature, the individuals standing between Christianity and paganism have usually been referred to as semi-pagans, crypto-pagans, or nominally Christians. In this article, a new concept incerti will be developed in order to illustrate the impossibility of strict dichotomies and to refer to unclassifiable and indefinable individuals in the borderland between pagans and Christians. Several examples of incerti individuals will be introduced in order to illustrate moments of ambiguity in Late Antiquity. In the historical background of Augustine’s De civitate Dei, there was also an incertus, a learned senator Volusianus. The most famous binary opposition, Augustine’s division of humankind into the city of God and the terrestrial city will also be discussed in this article.